Evaluation of An e-learning Scenario for Biomedical Engineers - Jan, Kožuško; Julia, Kuβ; Anja, Abdel-Haq; Claudia, Weichelt; Hans, Dietrich; Susanne, Hebestadt; Inge, Rudolph; Ute, Morgenstern (Procedia, social and behavioral sciences, 2012)
The new co-operative blended learning concept is being developed under leadership of the TU Dresden team with collaborative partners in S axony. In th e new e-learning system TheraGnosos - Biom edical Engineering, a new framework and feedback scenario have been developed. This has been compared with the previous version of e–learning software Labyrinthos -Medical Terminology, in which immediate feedback was implemented. 20 students studied for exam, using the old version, and 28 could use the new one. The average exam result in the first group was 2.26, and in the second group 1 .72. In control exam in another subject, there was no significan t improvement of score. The new developed feedback scenario might influence the learning effect, measured by exam score.